Ostatnie lata przedrozbiorowej Rzeczypospolitej - Sejm Wielki i konfederacja targowicka - Rafałowski, Hubert (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The government act, also known as the May 3rd Constitution of 1791, introduced a number of solutions to improve the functioning of the state. These changes did not meet with the approval of some magnates, which, fearing for their own interests, decided to establish the Confederacy of Targowica. It was aimed at overthrowing the May 3rd Constitution and returning to the status quo ante. Its participants turned to the Russian Empress Catherine II with a request to help them. Their postulates were approved by the empress on April 27, 1792 in St. Petersburg. These actions led to the Polish-Russian war, also known as the war in defense of the May 3 Constitution. The significant advantage of the Russian army, as well as the few successes of the Polish army, led to the accession of King Stanisław August Poniatowski to the Confederacy of Targowica on July 24, 1792. The people of Targowica have withdrawn from the changes introduced in the Constitution of May 3. Ultimately, this resulted in the signing of the partition treaty by Russia and Prussia on January 23, 1793, which the Grodno Sejm approved on June 17 of that year. The confederacy of targowica was finally dissolved on September 15, 1793, and its participants left the country or headed for their own land estates. During the Kościuszko Insurrection, most of the members of the confederation were lynched. They were sentenced to death by hanging, and the absentees were punished in effigie.
Keywords: Konstytucja 3 Maja 1791; konfederacja targowicka; insurekcja kościuszkowska